Explosives Analysis Using Thin-Layer Chromatography–Quantum Cascade Laser Spectroscopy - John R. Castro-Suarez; Luis A. Pérez-Almodóvar; Doris M. Laguer-Martínez; José L. Ruiz-Caballero; José A. Centeno-Ortiz; Tamara Felix-Massa; Leonardo C. Pacheco-Londoño; Samuel P. Hernández-Rivera (Molecules)
A new hyphenated technique using thin-layer chromatography (TLC) to separate analytes in mixtures, coupled with mid-infrared (MIR) laser spectroscopy for identification and quantification, is presented. The method, which provides a means for rapid screening of analytes that is practical, low-cost, fast, robust, and reproducible, was tested using nitroaromatic and aliphatic nitro high explosives (HEs) as target analytes. HEs are anthropogenic contaminants containing an -NO2 group. For validation of the new technique, a direct comparison of the 2,4,6-trinitrotoluene (TNT) spectrum, obtained by attenuated total reflection-Fourier transform infrared (ATR-FTIR) spectroscopy coupled with TLC, was carried out. The MIR laser spectroscopy-based method was evaluated by calculating the analytical figures of merit regarding the calibration curves’ linearity and the method’s sensitivity and precision. The TNT spectrum obtained by the MIR laser method showed two prominent and characteristic bands of the explosive at approximately 1350 cm−1 and 1550 cm−1 compared to the spectrum acquired by ATR-FTIR. The detection limit calculated for TNT was 84 ng, while the quantification limit was 252 ng. Multivariate analysis was used to evaluate the spectroscopic data to identify sources of variation and determine their relation. Partial least squares (PLS) regression analysis and PLS combined with discriminant analysis (PLS-DA) were used for quantification and classification. The new technique, TLC-QCL, is amenable to a smaller footprint with further developments in MIR laser technology, making it portable for fieldwork.